PATTERN OF MALIGNANT RENAL TUMOURS USING 2004 WHO CLASSIFICATION OF RENAL TUMOURS ON RADICAL NEPHRECTOMY - Murtaza, Badar; Mahmood, Arshad; Akmal, Muhammad; Ahmad, Hussain; Niaz, Waqar Azim; Khadim, Muhammad Tahir (Journal of Ayub Medical College Abbottabad, 2011)
Objective: To determine the type of malignant renal tumours subjected to radical nephrectomy at a tertiary care urology unit using the 2004 WHO classification for renal tumours. Methods: It was an observational study conducted at Department of Urology, AFIU Rawalpindi, from October 2008 to September 2010. The study included 92 patients with malignant renal tumours of both genders aged above 15 years. The histopathological types and grades were recorded along with the gross tumour presentation. The data was entered in structured proforma and analysed for descriptive statistics using SPSS-14. Results: Over the span of 24 months study, 92 cases of malignant renal tumours were subjected to radical nephrectomy. The age was 16-82 (57.23±14.61) Years and male to female ratio was 2.1:1. The lesions were mostly unifocal (96.7%) and 58.6% affecting the right side. The commonest malignant renal tumour encountered was the conventional clear cell renal carcinoma (78.2%). The other tumours in descending order were the transitional cell carcinoma (7.6%), papillary (chromphilic) renal cell carcinoma (6.5%), renal cell carcinoma unclassified (3.2%), chromophobe renal cell carcinoma (2.1%), Wilm’s tumour and oncocytoma (1.7%). T1 lesions were found in 42 cases (45.6%), T2 lesions in 25 cases (27.1%), T3a lesions in 17 cases (18.4%) each, while 8 cases (8.6%) had T3b lesions. Four cases had high and 3 had low grade lesions in transitional cell carcinoma. Wilm’s tumour had favourable prognosis, 1 case had oncocytoma limited to kidney. Among the rest, 26 (28.2%) were G1, 35 (38%) were G2, 16 (17.3%) were G3, and 6 (6.5) were G4. Conclusion: The commonest type of the malignant renal neoplasm remains the clear cell (conventional) renal cell carcinoma. The lesions from T1 to T3 are amenable to radical nephrectomy and may not include the ipsilateral adrenalectomy as well. The grade may range from G1 to G4. Keywords: Clear cell carcinoma, Radical nephrectomy, Transitional cell carcinoma